2015
DOI: 10.1530/erc-14-0537
|View full text |Cite
|
Sign up to set email alerts
|

Germline and somatic SDHx alterations in apparently sporadic differentiated thyroid cancer

Abstract: Along with breast and endometrial cancers, thyroid cancer is a major component cancer in Cowden syndrome (CS). Germline variants in SDHB/C/D (SDHx) genes account for subsets of CS/CS-like cases, conferring a higher risk of breast and thyroid cancers over those with only germline PTEN mutations. To investigate if SDHx alterations at both germline and somatic levels occur in apparently sporadic breast cancer and differentiated thyroid cancer (DTC), we analyzed SDHx genes in following 4 groups: 1) 48 individuals … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 37 publications
0
27
0
1
Order By: Relevance
“…During the process of revision of the present manuscript, a new publication by Ni et al [10] documented a significant frequency of germline mutations in SDHx genes among patients with differentiated thyroid carcinoma. Actually, the authors observed 48 cases among 754 (6 %) with germline SDHx mutations contrasting with 0/350 controls.…”
Section: Papillary Thyroid Carcinomamentioning
confidence: 76%
See 1 more Smart Citation
“…During the process of revision of the present manuscript, a new publication by Ni et al [10] documented a significant frequency of germline mutations in SDHx genes among patients with differentiated thyroid carcinoma. Actually, the authors observed 48 cases among 754 (6 %) with germline SDHx mutations contrasting with 0/350 controls.…”
Section: Papillary Thyroid Carcinomamentioning
confidence: 76%
“…Papillary histology is the major subtype among SDHx variant carriers with thyroid cancer in Cowden syndrome like cases, in contrast to the over-presentation of follicular histology in PTEN mutation carriers [9,10].…”
Section: Papillary Thyroid Carcinomamentioning
confidence: 95%
“…By analyzing the expression of the SDHx gene in differentiated carcinoma samples, a classic PTC histology was overrepresented among patients with low overall SDHx expression compared with those with other histologic types, especially the follicular variant form of PTC [42]. …”
Section: Discussionmentioning
confidence: 99%
“…About 6% of thyroid cancers have a germline mutation of SDHB or SDHD and a further 5% have somatic SDHC mutations. 30 Consistent loss of either SDHC or SDHD gene expression is associated with earlier disease onset and higher pathologic TNM stage in both papillary and follicular thyroid tumors. 30 Although further studies focusing on the SDH transcript levels and immunohistochemical SDHB protein expression are to be fully explored, early studies point toward papillary histology as the major subtype.…”
Section: Other Sdh-deficient Tumorsmentioning
confidence: 95%